Inequality, Growth and Welfare: An International Comparison - Jesús Ruiz-Huerta; Rosa Martínez; Luis Ayala (Luxembourg Income Study (LIS), 1999)
This study offers will try to present some empirical evidence in an attempt to improve our understanding of welfare. After reviewing the empirical criteria used to measure welfare in comparative contexts and explaining our methodology (section 2), section 3 deals with major trends in some OECD countries. In section 4, the effects on welfare of the distribution of economic growth by income levels are analyzed using real income changes at three different points of the distribution scale. A cross-national comparison of the absolute income levels of the low, median and high-income households in every country is carried out in section 5. Finally, in the last part of the paper, our attention is focused on a synthetic measure of welfare based on the notion of combining average income and inequality in some kind of two-dimensional welfare index.
Keywords: 330; Einkommensverteilung; Sozialstaat; Messung; Wirtschaftswachstum; Wohlfahrtsanalyse; OECD-Staaten